FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Denisha, Michelle; Widyasari, Widyasari (Jurnal Paradigma Akuntansi, 2024)
This study aims to determine the effect of total asset turn over, investment opportunity set, liquidity, and profitability on dividend policy using profitability as moderating variable. The research is based on documentation of the basic industry and chemicals listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020. The research finds that total asset turn over has a positive and significant effect on dividend policy, investment opportunity set has a negative and insignificant effect on dividend policy, liquidity has a negative and insignificant effect on dividend policy, profitability has a positive and significant effect on dividend policy, profitability is able to moderate the influence of total asset turn over on dividend policy while profitability is not able to moderate the influence of investment opportunity set and liquidity on dividend policy.